Research on Data Transfer Method for Multi-physics Coupling Based on Unstructured Mesh Monte Carlo - LI Rui1, LIU Shichang1, WANG Lipeng2, WANG Zhenyu1, CHEN Yixue1 (Yuanzineng kexue jishu, 2025)
In the design and optimization of reactors, to ensure their safe and reliable operation, a multiphysics coupling analysis is necessary. Among these, the neutronic-thermal-mechanical coupling and neutronic-thermal-fluid coupling analyses have a significant impact on the reactor design. In addressing the data transfer issues in the multiphysics coupling process of reactors, this study employs a hybrid approach that integrates unstructured mesh (UM) Monte Carlo with finite element methods. In the coupling process, data transfer is extensive and repetitive. This study utilizes the ABAQUS script interface, written in Python, to handle these tasks. The script interface acts as a manager in the process, extracting power data from the output files of the UM Monte Carlo neutron transport code, processing it to obtain the volume heat flux. This volume heat flux is then passed as input to ABAQUS for further calculations. After ABAQUS completes its computations, the script interface extracts relevant data from the output files, including temperature, displacement and volume, and transfers this information back to the UM Monte Carlo neutron transport code. This seamless integration of data between the two codes ensures that the integrity and accuracy of the multiphysics simulation are maintained. For the neutronic-thermal-mechanical coupling problem, a surface-UM Monte Carlo method was adopted. The calculations were performed by coupling the RMC with the heat transfer and expansion modules of ABAQUS. This method was applied to a case of the Godiva-Ⅰ pulsed reactor. The calculation process included the following steps: the power distribution calculated by RMC was transferred to ABAQUS for calculations to obtain the mechanical expansion of the reactor; subsequently, RMC was used to perform calculations on the expanded reactor model to assess the reactivity feedback. The results show that the discrepancy in peak temperature is within 1 K, and the discrepancy in the negative reactivity feedback is 0.87%. For the neutronic-thermal-fluid coupling issues, a volume-UM Monte Carlo method was employed. The calculations were performed by MCNP and the heat transfer and CFD modules of ABAQUS. This method was applied to a case of the sodium-cooled fast reactor fuel pin. The calculation process included the following steps: the power distribution calculated by MCNP was transferred to ABAQUS for convection heat transfer calculations, and then the fuel temperature and fluid density were fed back to MCNP for further computations. The results show that the maximum temperature discrepancy from the literature is within 1 K. These two processes maintain model consistency throughout the calculation process, ensure precise data transfer, and take into account the impact of solid thermal expansion, fuel temperature, and fluid density on neutron physics, providing a reference for the multiphysics coupling analysis of reactors.